2023
DOI: 10.1101/2023.01.16.23284614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long term follow-up of colorectal cancer screening attendees identifies differences inPhascolarctobacterium spp. using 16S rRNA and metagenome sequencing

Abstract: Background: The microbiome has been implicated in the initiation and progression of colorectal cancer (CRC) in cross sectional studies. However, there is a lack of studies using prospectively collected samples. Methods: We analysed 144 archived faecal samples from participants in the NORwegian Colorectal CAncer Prevention (NORCCAP) trial diagnosed with CRC or high-risk adenomas (HRA) at screening, or who remained cancer-free during 17 years of follow-up. We performed 16S rRNA sequencing of all samples, and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Several studies have reported similar associations at the genus level 13, Peters, 201613, Peters, #1244 , with few having looked at species level. Both our previous work including 17 years of follow-up 5 , and Yachida et al 12 found increased abundance of P.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Several studies have reported similar associations at the genus level 13, Peters, 201613, Peters, #1244 , with few having looked at species level. Both our previous work including 17 years of follow-up 5 , and Yachida et al 12 found increased abundance of P.…”
Section: Discussionmentioning
confidence: 52%
“…Succinyl-CoA is the intermediate compound of succinate in the TCA cycle and is released upon production of an ATP molecule 78 . In our previous work we showed a lower abundance of several pathways related to heme biosynthesis in high risk adenomas compared to healthy controls 5 .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The gut virome has also been associated with diseases such as inflammatory bowel disease and type 2 diabetes 15,16 . Dysregulation of gut bacteria and abundance of certain bacteria [17][18][19] are also proposed features of the association between the gut microbiome and 3 colorectal cancer development 20 . These changes in the bacteriome are likely to be accompanied by phage dysregulation 21 .…”
Section: Introductionmentioning
confidence: 99%